Optimization Tools for Meeting Nutrient Requirements of Indian Children and Adults at Optimal Cost - Fathima Ayoob; Jawahar R Manivannan; Ashikh Ahamed; Afsal K Murikkanchery; Abhishek Kumar; Santu Ghosh; Patrick Webb; Anura V Kurpad; Tinku Thomas (Public Health Nutrition)
Abstract